1995
DOI: 10.3354/ame009003
|View full text |Cite
|
Sign up to set email alerts
|

Some environmental aspects of marine hydrocarbon bacteriology

Abstract: This paper reviews some of the field aspects of hydrocarbon bacteriology in the marine environment. The first section recapitulates the current position with regard to the input of polluting oil into the sea and the main environmental factors which govern the rate of oil breakdown. The second deals with the 1991 oil spill during the Gulf War and what is known about the bacteriology of that area, together with some recent data from Japan. Thirdly a critical review of the theory and practise of bioremediation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 26 publications
(30 reference statements)
1
12
0
3
Order By: Relevance
“…However, one exception can be noted (diesel oil + Inipol mesocosm) where the optimum temperature was below 20°C. It is reasonable to assume that the limiting factor was the temperature characteristics of the enzymes that carry out the initial oxidative steps (Floodgate, 1995). In the present study, similar bacterial numbers were observed at three different temperatures.…”
Section: Discussionsupporting
confidence: 74%
“…However, one exception can be noted (diesel oil + Inipol mesocosm) where the optimum temperature was below 20°C. It is reasonable to assume that the limiting factor was the temperature characteristics of the enzymes that carry out the initial oxidative steps (Floodgate, 1995). In the present study, similar bacterial numbers were observed at three different temperatures.…”
Section: Discussionsupporting
confidence: 74%
“…Various microbial genera have been described as being able to degrade petroleum hydrocarbons. Of these, some like Pseudomonas, Vibrio, Acinetobacter, Flavobacterium, Rhodococcus, Nocardia, Achromobacter and Corynebacteria are well known by their ability to use the hydrocarbons in water (Brooks et al, 1978;Floodgate, 1995;Cury, 2002;Widada et al, 2002;Baek et al, 2007;Rodrigues et al, 2009;Kostka et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Not all microbes can break down all DOM (Floodgate, 1995). The oceanic DOM pool represents a continuum of biological lability, ranging from refractory material that turns over on time scales of centuries to millennia (Williams and Druffel, 1987;Bauer et al, 1992) to more available material turning over on time scales of minutes to days (Cherrier et al, 1996;Carlson, 2002).…”
Section: Lability (Availability) Of Dommentioning
confidence: 99%